Determinants of Mental Health in Adolescents Aged 11-18 Years in Padang - Yulia Yulia; Gusni Rahma; Fadhilatul Hasnah; Syukra Alhamda (JIK-JURNAL ILMU KESEHATAN, 2024)
Adolescent mental health is a crucial issue in the individual and social development of teenagers. Several studies report a prevalence of mental disorders among teenagers of around 20-30%. The Basic Health Research (Riskesdas) indicates that more than 19 million people over the age of 15 experience emotional mental disorders. Various challenges faced during adolescence can affect mental health, both from internal and external factors. Thus, understanding the determinants of adolescent mental health is essential to develop effective interventions. This study aims to identify the determinants that influence the mental health of adolescents aged 11-18 in Padang City. This is a quantitative study with a cross-sectional design. The sample consisted of 180 adolescents aged 11-18 years in the working area of Puskesmas X in Padang City, selected through random sampling. Data collection was conducted online using a questionnaire via Google Forms. The Strengths & Difficulties Questionnaire (SDQ) measured adolescent mental health disorders. Multivariate analysis was performed using logistic regression. The results show that 43.9% of adolescents have poor mental health. The most significant determinant influencing adolescent mental health is a history of bullying (PR 2.84; 95%CI=1.46-5.52). Adolescents with a history of bullying are 2.84 times more likely to experience mental disorders compared to those without such a history. Preventing mental disorders in adolescents requires a comprehensive approach, including the role of parents in parenting, the role of schools in preventing bullying in the school environment, peer support, and access to youth-friendly counseling services.